Potential of Bamboo in Vegetative Embankment - Kaushik, P. K.; Tripathi, Y. C.; Pandey, B. K. (Indian Forester, 2005)
The Brahmaputra basin in India, particularly its valley in Assam, represents an acutely flood-prone region and occurrence of flood has been an age-old phenomenon in the riverine areas. During the rainy season, the rivers not only become filled up with water, but the excess amount of water also spill over their banks flooding their neighbouring regions. At the same time bank erosion occurs in almost all the large rivers destroying human habitats and their crop fields. The greatest single casualty due to recurrent floods, accounting for as much as 75 per cent of the total flood loss is the agricultural sector which happens to be the mainstay of the economy. Accelerated erosion due to deforestation and increased pressure on land due to explosion of population is a major cause of this increase in sediment yield. Biological means of protection against erosion are the cheap and simple practical solution that must be technically suitable for different conditions, economically viable with respect to the cost of both initial establishment/maintenance, ecofriendly, people-oriented and sustainable. Vegetative embankment models based on Bamboo and other species endemic to the northeast region can be a cost effective and sustainable solution to the alarming problem of soil stabilization and river bank erosion. The paper presents the various a!tpects of bank erosion in BrahmaputraValley and suggests vegetative controls for talking the problem.